Prioritizing factors influencing global network readiness index with bayesian belief networks - Abroon Qazi (Journal of Open Innovation: Technology, Market and Complexity)
The rapid evolution of digital transformation necessitates a comprehensive understanding of national digital readiness. The Network Readiness Index (NRI) serves as a key benchmark for assessing a country's preparedness to leverage digital technologies for economic and societal development. This study uses Bayesian Belief Network (BBN) models to systematically analyze and prioritize the factors influencing the NRI, using data from 134 countries in 2023. Unlike existing studies that primarily adopt conventional techniques, assuming the NRI drivers as independent, this research provides a probabilistic assessment of the interdependencies between the four NRI pillars—technology, people, governance, and impact—and their respective sub-pillars. The findings indicate that 'technology', 'impact', and 'people' are the most influential pillars in shaping digital readiness outcomes, with 'businesses' and 'trust' emerging as critical sub-pillars. The study enhances the existing literature by introducing a predictive framework that informs policymakers and industry leaders on the key levers for improving national digital competitiveness. By offering a network approach to prioritizing digital readiness factors, this research contributes to more effective policy design, strategic investments, and sustainable digital transformation efforts.